The Zoonoses Database-A HyperCard™ Stack on the Macintosh™ Computer for Teaching Veterinary Epidemiology and Public Health - Hungerford, Laura L. (1990)
For the past 2 years second-year veterinary students have used a HyperCard-based Zoonoses Database to abstract, store and retrieve information on zoonotic diseases. Each student was required to review the veterinary literature for information about one zoonotic disease and enter the information into a HyperCard template which summarized epidemiologic aspects of the disease. A total of 99 diseases are included in the Zoonoses Database. To use this resource in problem-solving, students formed mock 2 to 6 person veterinary practices. Student “practice groups” were then assigned one of 24 case histories and asked to form a rule-out list, select the most probable disease, and provide advice to the client regarding the zoonotic potential of the disease in question. We will continue to expand the database and link life cycles to it.